DIFFERING OPINIONS DO NOT SPOIL FRIENDSHIPS: MANAGING PUBLIC–PRIVATE PARTNERSHIP (PPP) INFRASTRUCTURE PROJECTS IN JORDAN. (11th July 2013) - Mistarihi, Ali; Hutchings, Kate; Shacklock, Arthur
SUMMARY This research investigates the approaches, strategies and challenges facing the management of the implementation phase of public–private partnership (PPP) projects in Jordan. Jordan is a newer but common user of PPPs in the Middle Eastern region, where PPPs not only are of economic strategic importance but also entail significant investment risk given resource scarcity. This research involves semi‐structured interviews with senior managers representing different partnering organisations in two case study organisations in Jordan. The research finds that, despite the management difficulties confronting PPP managers, strategies adopted by them limit the impact of these challenges. The research makes an important theoretical contribution in providing a detailed analysis of effective PPP management approaches in response to difficulties at the implementation phase, which had not been systematically explored in extant PPP research, and broadens PPP research to the Jordanian context. Moreover, the research contributes greater understanding of how partnerships should be effectively managed. Copyright © 2013 John Wiley & Sons, Ltd.